A HOSPITAL BASED AUTOPSY STUDY OF 50 CASES AT COMBINED MILITARY HOSPITAL (CMH), SIALKOT: Autopsy Study of 50 Cases - Asif, Naveed (Pakistan Armed Forces Medical Journal, 2014)
Objective: To analyze the pattern of deaths on autopsy carried out on Armed Forces personnel in CMH Sialkot.Study Design: Retrospective analytical studyPlace and Duration of Study: Combined Military Hospital Sialkot (CMH), from 2009 to 2012Materials and Methods: In a total of fifty (50) cases detailed postmortems were carried out and gross features on external examination and different systemic examinations were recorded. Histopathology of various organs was done in all cases. Chemical and toxicological examination of various abdominal viscera was carried out in all sudden and suspicious deaths.Results: Ischemic Heart Disease (IHD) was most common cause of death (38%) followed by road traffic accidents (14%) and electrocution (8%). Sudden adult death syndrome accounted for 4 cases of deaths. Other causes were drowning, cerebral malaria, heat stroke, gunshot wounds, myocarditis, brain hemorrhage, meningitis and diabetic ketoacidosis. Most of these cases were young soldiers (n=30) followed by Non-Commissioned Officers (n=17).Conclusion: A large number of our young soldiers dying of heart problems is an alarming situation. Awareness among the troops of various risk factors is most important. Precautionary measures against preventable causes should be taken.